Effect of Bunch Feeding on Yield Parameters of Banana cv. Grand Naine in Ratnanagar, Chitwan, Nepal - Shrestha, Shrisha; Bhattarai, Sabin; Tamang, Palsang; Ranabhat, Anu (International Journal of Applied Sciences and Biotechnology, 2023)
A field experiment consisting of bunch stalk feeding with different treatments on yield of banana cv. Grand Naine (G9) was conducted during 2022 in Ratnanagar-12, Jamunapur of Chitwan, Nepal. The experiment was laid in Random Complete Block Design (RCBD) with 7 treatments and 3 replications. Bunch fed with dipping the cut end in the combination of 500gm cow dung + 10g urea + 20g SOP + 15mg of GA3 + 100ml water resulted significantly higher finger length (20.36 cm), finger weight (0.18kg), finger diameter (36.28mm, bunch length (101.90 cm), bunch weight (32.37 kg), peel weight (19.05 g). and pulp weight (82.39 g) compared with control (without bunch stalk feeding). Thus, the research shows that the bunch feeding with 500gm cow dung, 10g urea, 20g SOP and 15mg of GA3 improves yield parameters of banana cv. Grand Naine. Int. J. Appl. Sci. Biotechnol. Vol 11(1): 25-29.